Pharmacokinetics and analgesic efficacy of fentanyl and buprenorphine in chicken embryos - Luis Truhlar; Julia Werner; Marie-Louise Schmid; Aylina Glasenapp; Heike Baehre; Judith Reiser; Julia Koerner; Heidrun Potschka; Marion Bankstahl; Christine Baumgartner (PLoS ONE, 2026)
Chicken embryos are able to process and receive noxious stimuli from embryonic day (ED) 13. In the context of animal welfare, analgesic refinement is highly recommended for painful procedures from this time onwards. In this first study, the pharmacokinetic and pharmacodynamic profiles of the opioid analgesics fentanyl (0.2 mg/kg) and buprenorphine (0.5 mg/kg) were studied in ED17 chicken embryos. Analgesic plasma concentrations were determined at different time points after administration via LC-MS/MS. In a validated model of mechanical nociception in chicken embryos, analgesic efficacy and potential side effects were determined based on mean arterial blood pressure, heart rate, beak, and body movements. Maximum mean plasma levels of 37.55 ng/ml (fentanyl) and 144.17 ng/ml (buprenorphine) were reached at 15 min with a plasma elimination half-life of around 75 or 60 min, respectively. No side effects on the cardiovascular system and no alterations in body movements, reflecting possible sedative effects, were detected. No significant reduction in mean arterial pressure after noxious stimulation of the base of the beak following opioid analgesic treatment was observed. However, medium to large effect sizes may suggest potential clinical importance. A significant reduction in wide beak opening, a nociceptive behavioral parameter, was observed 15 min after administration of fentanyl. In conclusion, both opioids may have potential as safe analgesic options for the use during potentially painful procedures in chicken embryos, although further research is needed to fully demonstrate their clinical efficacy.